The Efficiency Of Cauliflower Farm In Sumber Bening Village Selupu Rejang Sub District Rejang Lebong Regency - Rita Feni; Irma Irmeliani (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2022)
Cauliflower is one of horticulture vegetable which has potential to be cultivated by farmer, because of it’s price is higher than other vegetables on the market. This study aims to analyze the efficiency of cabbage farm in Sumber Bening village Selupu Rejang Lebong Regency. This study used census method by using all 22 cauliflower farmers as respondent. Data used in this study is primary and secondary. Data analyzed using quantitative and qualitative method. This study result shows that revenue of cauliflower farmer is Rp 1.675,628,75 per season. Efficiency value or R/C ratio is 1.36, BEP 769,82 kg and Rp 4.402,78